ANALISIS KEPRIBADIAN TOKOH DALAM CERPEN NYAYIAN IBU KARYA ERWIN SETIA - Defi Restiawati; Cintya Nurika Irma (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2022)
This research aims to describe the personality of the character in the short story Mother Song by Erwin Setia. The approach used in this research is the literary psychology approach. The data source in this study is the short story Nyayian Ibu by Erwin Setia which was accessed online on hot.detik.com published in 2021. The data analysis technique in this study is a reading and note technique, namely reading repeatedly the short story Nyayian Ibu erwin Setia and record the results of the findings according to the variable problems in the form of personality figures in short stories. The results of this study are conveyed through the words and sentences contained in the short story. From the short story of Nyayian Ibu by Erwin Setia there are three psychiatric structures of a person contained in the literary psychology proposed by Simund Freud, namely (1) id, which is felt directly by the mother figure appears naturally, because of the impulse of isting and also implosife to do a humming activity (2) ego, found in the figure of mother and child. The ego found in the mother figure is humming by using his own essay only for pleasure and momentary pleasure. While the ego contained in a child named Raega is a child who wants to continue to find out about the circumstances of his mother who has different habits, and (3) superego, there is a figure raega who has a strong stance, but Raega can also consider the good and bad something he will do. Keywords: personality, short stories, literary psychology